Role of aromatic localization in the gating process of a potassium channel. - Domene, C; Vemparala, S; Klein, M; Vénien-Bryan, C; Doyle, D (2006)
Position of the transmembrane aromatic residues of the KirBac1.1 potassium channel shifts from an even distribution in the closed state toward the membrane/solute interface in the open state model. This is the first example of an integral membrane protein making use of the observed preference for transmembrane aromatic residues to reside at the interfaces. The process of aromatic localization is proposed as a means of directing and stabilizing structural changes during conformational transitions within the transmembrane region of integral membrane proteins. All-atom molecular dynamics simulations of the open and closed conformers in a membrane environment have been carried out to take account of the interactions between the aromatic residues and the lipids, which may be involved in the conformational change, e.g., the gating of the channel.